Digital cities between history and archaeology - Forte, Maurizio 1961-; Murteira, Helena 1956- (Oxford scholarship online, 2020)
The guiding premise of this work is the role of the study of the city, its display and dissemination, in the information network of digital cities. A collection of essays on the ways the city can now be studied and presented, this text surveys the current situation in regard to various visualizations of cities of the past and present, built on historical evidence and scientific hypothesis. The chapters reflect the authors' wide-ranging fields of interest and experience, from archeology to urban planning